Study on The Condition of Coral Reefs in The Planned Marine Park Area of Kaliage Besar Island, Kepulauan Seribu National Park, DKI Jakarta - Hermansyah Hermansyah; Tatang Mitra Setia; Cipto Utomo; Isai Yusidarta; Annastasya Rahma Ramadhani; Alvira Noer Effendi; Nurdian Sahrila (Journal of Tropical Biodiversity, 2021)
Kaliage Besar Island is one of the islands in Seribu Islands National Park, DKI Jakarta. Located in the Management Section of Kelapa Island Region I National Park. The island with the allotment of the use rights of the private island which is used as a public tourist and resort. Kaliage Besar Island still has the potential for highly productive coral reef resources. Currently, the coral reefs of Kaliage Besar Island has suffered damage caused by anthropogenic activities and natural factors. This research used Underwater Photo Transect/UPT method were analyzed using CPCe 4.1. software (Coral Point Count with Excel extension). Data collection was carried out at one research point with a depth of 3 m and a transect length of 20 m with 3 data collection times (10 m intervals between transects). The measurement physico-chemical parameters results was shown that water quality in Kaliage Besar Island was still within tolerance limits for coral life. The percentage of live coral cover was in a bad category with a low value 6,46%. Composition of hard coral genusis consists of 6 family, 7 genus, and 119 individuals. The most dominant genus is Porites with submassive and massive growth form. The index value of diversity shows a low category (0,42). The dominance index value showed a high category (0,84). Uniformity and mortality index value showed a low category (0,22 and 0,28).